What predicts mental health profiles in first-generation college freshmen?: the role of proactive personality and university environment - Ru Chen; Xin Gao; Zekun Zhang; Mingxue Hong; Lulu Zhang (BMC Psychology)
Abstract Background The mental health of first-generation college students has received much attention from researchers. The dual-factor model of mental health emphasizes the integration of psychopathology and well-being to achieve a comprehensive assessment of mental health. Previous research has focused on the psychopathology and well-being of first-generation college students in isolation while ignoring the overall mental health development. Aim This study aims to identify the mental health profiles of first-generation college freshmen (indexed by symptoms of psychopathology and well-being) using a person-centered approach, and examine direct and interactive associations of proactive personality and university environment with mental health profiles. Method This study included 557 first-generation college freshmen recruited from universities in China. Participants completed measures assessing proactive personality, university environment, mental health continuum, and depression, anxiety, and stress. Latent profile analysis, multinomial logistic regression, and simple slope analyses were used to investigate these relationships. Results The results revealed four mental health profiles, namely flourishing mental health, moderate mental health, content-dominated but symptoms, and symptoms-dominated but content. A multinomial logistic regression analysis revealed that first-generation college freshmen with higher proactive personality and university environment were more inclined to fall into the flourishing mental health profile compared to other sub-optimal mental health profiles. The interaction term between proactive personality and university environment was significant. Specifically, compared to proactive first-generation college freshmen in high levels of university environment, those in low levels of university environment were more inclined to be categorized into the flourishing mental health profile rather than the symptoms-dominated but content profile. Conclusion These results underscore the diverse nature of mental health changes in first-generation college freshmen, underscoring the need for tailored prevention strategies.